A systematic review and meta-analysis on the global prevalence of helminthic parasites among schoolchildren: a public health concern - Milad Badri; Meysam Olfatifar; Zahra Gharibi; Mahendra Pal; Kareem Hatam-Nahavandi; Ali Asghari; Giovanni Sgroi; Hanieh Soltani; Amir Abdoli; Aida Vafae Eslahi (BMC Public Health)
Abstract Background Neglected tropical diseases (NTDs) are responsible for substantial illness and death worldwide. Helminthic infections among school-aged children pose a serious public health challenge due to their detrimental effects on health and development. Methods A wide-ranging search conducted across five databases, including Scopus, EMBASE, PubMed, Web of Science, and Google Scholar to retrieve papers published between 1998 and 2024. To evaluate the combined prevalence, a random-effects model with a 95% confidence interval (CI) was applied, and the statistical analysis was performed using meta-analysis packages in R version (3.6.1). Results There were 190 eligible studies documented in 42 countries, and 199,988 schoolchildren included in this review. The global prevalence of helminthic parasites was 20.6% (17.2– 24.3%). Among the countries studied, Tanzania and Vietnam showed the highest levels of prevalence at 67.41% and 65.04%, respectively, with Toxocara spp. and Ascaris lumbricoides being the most prevalent helminthic parasites at 10.36% and 9.47%, respectively. Conclusion In conclusion, this study underscores the pressing public health concern of helminthic infections among schoolchildren, largely driven by inadequate sanitation and poor water quality. Prompt action, such as improving sanitation, expanding school-based deworming programs, and enhancing access to safe water, is crucial to control these infections and enhance overall health outcomes.